Tenney - Hertz, Kellen (Hertz, Kellen. Tenney (Series), 2017)
When aspiring songwriter Tenney gets invited to perform at Nashville's famed Bluebird Café, her parents decide she's too young to perform professionally, leaving her future hanging in the balance.